Biblical Authority and Moral Tensions in a Polish Catholic Migrant Community in Denmark - Michael Brixtofte Petersen (Religions)
The Catholic Church in Denmark hosts several migrant communities, with the Polish-speaking group among the largest and most visible. Institutionally, Catholic priests from Poland serve as chaplains for migrant congregations, accompanying these mobilities and providing educational practices (e.g., family guidance, biblical teaching). This paper examines how perspectives on Catholic scriptural authority differ between the Church’s institutional representatives and its members, revealing tensions between biblical authority, social accommodation, and family values in a migratory setting. Based on 20 months of fieldwork in a Polish Catholic community in Copenhagen, this paper highlights the dynamic interplay of how Church members assess scriptural authority as evaluative engagement in their transnational lives in the Danish public sphere, illustrated through interconnected ethnographic excerpts. This article illustrates how scriptural engagement offers a productive lens to explore divergent notions of Polish Catholic diasporic life and the tensions between transnational religion, national belonging, and moral navigation.